Demography and Ethics in Ecodevelopment – Chances and Threats - Jedynak, Stanisław (Problemy Ekorozwoju, 2007)
The article is a reflection on possible solutions for the growing problem of Earth’s overpopulation. This is a threat to the whole ecosphere and must be considered as a problem of the immediate future. Attempts to avoid a demographic trap are presented in the form of various models concerning the optimal population of the Earth.